ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEMISKINAN DI KOTA MEDAN - Ramadhan, Faisal; Fadlan, Ahmad (Prodi Pendidikan Ekonomi Universitas Balikpapan, 2024)
Analysis of Factors Affecting Poverty in Medan City. The problems in this study are the Human Development Index, Economic Growth, Unemployment and Education are factors that affect poverty in Medan City. This study aims to analyze the factors that affect Poverty in Medan City. The data processed using factor test analysis then using multiple linear regression. Data obtained from the Central Statistics Agency (BPS) were processed using SPSS Software Version 22.0 For Windows. The results of the study showed that of the 4 variables analyzed with the multiple linear regression analysis model, it showed that the Human Development Index, Economic Growth, and Unemployment had a significant effect on Poverty in Medan City.